If θ = 1 3 π , determine the value of the reciprocal of
cos θ cos 2 θ cos 3 θ cos 4 θ cos 5 θ cos 6 θ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that, previously we had the expression as product of cosines of angles in AP, which we converted into a product of cosines of angles in GP. It was only possible because 13 is relatively prime to 2, due to which we know that any integer power of 2, will have remainder that is also relatively prime to 13 when divided by 13. Since 13 was a prime to begin with, it was possible to convert all numbers smaller than it as a power of 2.
I also want to add 2 more solutions, but how do i do that? After writing this solution, i am not getting any options to write another.
Log in to reply
Nice solution! You only get one "space" to write a solution on here, but you can either add extra solutions in the comments, or you can divide up the main solution box by typing a single underscore character on a line, which gives you this:
...so you can have a different section. It'll make it easier to read if you write the solutions in LaTeX (I see you did for the question).
Thank you Chris, that was helpful.
x = cos θ cos 2 θ cos 3 θ cos 4 θ cos 5 θ cos 6 θ 1 = cos 1 3 π cos 1 3 2 π cos 1 3 3 π cos 1 3 4 π cos 1 3 5 π cos 1 3 6 π 1 = cos 1 3 π cos 1 3 2 π cos 1 3 4 π ( − cos 1 3 8 π ) cos 1 3 3 π cos 1 3 6 π 1 = sin 1 3 π cos 1 3 π cos 1 3 2 π cos 1 3 4 π cos 1 3 8 π cos 1 3 3 π cos 1 3 6 π − sin 1 3 π = sin 1 3 2 π cos 1 3 2 π cos 1 3 4 π cos 1 3 8 π cos 1 3 3 π cos 1 3 6 π − 2 sin 1 3 π = sin 1 3 4 π cos 1 3 4 π cos 1 3 8 π cos 1 3 3 π cos 1 3 6 π − 4 sin 1 3 π = sin 1 3 8 π cos 1 3 8 π cos 1 3 3 π cos 1 3 6 π − 8 sin 1 3 π = sin 1 3 1 6 π cos 1 3 3 π cos 1 3 6 π − 1 6 sin 1 3 π = − sin 1 3 3 π cos 1 3 3 π cos 1 3 6 π − 1 6 sin 1 3 π = sin 1 3 6 π cos 1 3 6 π 3 2 sin 1 3 π = sin 1 3 1 2 π 6 4 sin 1 3 π = sin 1 3 π 6 4 sin 1 3 π = 6 4 Since θ = 1 3 π Note that cos ( π − ϕ ) = − cos ϕ and sin ( π − ϕ ) = sin ϕ
Problem Loading...
Note Loading...
Set Loading...
Okay, we have 13θ=π, and we have to compute the given expression. Note that, since 13 is a prime number, it makes this process possible.
Let P=cos(θ)cos(2θ)cos(3θ)...cos(6θ).
Since, 13θ=π,
cos(5θ)=cos(5θ-13θ)=-cos(-8θ)=-cos(8θ).
Then, cos(3θ)=-cos(3θ+13θ)=-cos(16θ).
And also, cos(6θ)=cos(6θ+26θ)=cos(32θ).
Thus P=cos(θ)cos(2θ)...cos(32θ). This expression is actually a "telescopic product". For those who are not familiar with the concept, consider this,
sin(2θ)/(2sin(θ))=cos(θ),
sin(4θ)/(2sin(2θ))=cos(2θ), sin(8θ)/(2sin(4θ))=cos(4θ),
....
sin(64θ)/(2sin(32θ))=cos(32θ).
Multiply all these equations and you will get, sin(64θ)/(64sin(θ))=P. But again we write sin(64θ)=sin(65θ-64θ)=sin(θ). Thus we have, P=1/64 => 1/P=64.